An idiographic approach to idiopathic environmental intolerance attributed to electromagnetic fields (IEI-EMF) part I. Environmental, psychosocial and clinical assessment of three individuals with severe IEI-EMF - Dömötör, Zsuzsanna; Szabolcs, Zsuzsanna; Bérdi, Márk; Witthöft, Michael; Köteles, Ferenc; Szemerszky, Renáta (Heliyon, 2022)
IEI-EMF refers to an environmental illness whose primary feature is the occurrence of symptoms that are attributed to exposure to weak electromagnetic fields (EMFs). There is a growing evidence that this condition is characterized by marked individual differences thus a within-subject approach might add important information beyond the widely used nomothetic method. A mixed qualitative/quantitative idiographic protocol with a threefold diagnostic approach was tested with the participation of three individuals with severe IEI-EMF. In this qualitative paper, the environmental, psychosocial, and clinical aspects are presented and discussed (results of ecological momentary assessment are discussed in Part II of this study). For two participants, psychopathological factors appeared to be strongly related to the condition. Psychological assessment indicated a severe pre-psychotic state with paranoid tendencies, supplemented with a strong attentional focus on bodily sensations and health status. The psychological profile of the third individual showed no obvious pathology. Overall, the findings suggest that the condition might have uniformly been triggered by serious psychosocial stress for all participants. Substantial aetiological differences among participants with severe IEI-EMF were revealed. The substantial heterogeneity in the psychological and psychopathological profiles associated with IEI-EMF warrants the use of idiographic multimodal assessments in order to better understand the different ways of aetiology and to facilitate person-taylored treatments. Electromagnetic hypersensitivity; Idiographic; Clinical; Paranoid; Health anxiety; MMPI; Individual aetiology.